A NEW APPROACH TO MEASURE THE QUALITY OF UNIVERSITY SERVICES USING THE SERVPERF MODEL AND STATISTICAL TECHNIQUES IMPLEMENTED IN A BUSINESS INTELLIGENCE SOLUTION - HENRÍQUEZ, SANTIAGO DOMINGO MOQUILLAZA (2024)
IN ORDER TO CARRY OUT CONTINUOUS IMPROVEMENT IN UNIVERSITIES, IT IS NECESSARY TO INVESTIGATE WHAT INTERESTS THE STUDENT REGARDING THE QUALITY OF THE SERVICES THAT AFFECT STUDENT SATISFACTION, FOR WHICH A STUDY OF THE LITERATURE ON THE ATTRIBUTES THAT EMANATE FROM THE QUALITY OF SERVICES TO DEVELOP LATER THE RESEARCH INSTRUMENT MAKING USE OF THE SERVPERF MODEL IN ITS VARIOUS DIMENSIONS WHICH ARE: TANGIBILITY, SECURITY, EMPATHY, RELIABILITY, AND SENSITIVITY. TO OBSERVE THE LEVEL OF QUALITY BASED ON THE DATA OBTAINED, HYPOTHESES WERE RAISED, WHICH WERE VALIDATED WITH STATISTICAL TESTS USING THE IBM SPSS SOFTWARE. LIKEWISE, WITH THE DATASET OF THE PERCEPTION SURVEY, A BUSINESS INTELLIGENCE SOLUTION WAS IMPLEMENTED USING POWER BI DESKTOP, USED FOR THE DEVELOPMENT OF THE AGILE SCRUM METHODOLOGY, SO THAT IT CAN BE VISUALIZED IN A DASHBOARD FOR DECISION MAKING, THE LATTER BEING IMPORTANT SINCE NO STUDIES OF PERCEPTIONS OF BUSINESS MANAGEMENT HAVE BEEN FOUND IN THE REVIEWED LITERATURE. THE QUALITY OF UNIVERSITY SERVICES IMPLEMENTED IN A BUSINESS INTELLIGENCE SOLUTION, LIKEWISE, AS A CONSEQUENCE OF APPLYING THE EXPLORATORY AND CONFIRMATORY FACTOR ANALYSIS USING AMOS SOFTWARE, LATENT VARIABLES ARE GENERATED, WHICH ARE ALSO IMPLEMENTED IN THE BUSINESS INTELLIGENCE PLATFORM, WHICH CONSTITUTES THE NOVELTY OF THE RESEARCH WORK AND ADDITIONALLY TO PARTLY EXPLAIN THE NONCONFORMITIES, THE SENTIMENT ANALYSIS IS DONE IN PYTHON SO THAT THE UNIVERSITY EDUCATIONAL MANAGEMENT CAN OBSERVE AND CORRECT AND THEREFORE IMPROVE THE QUALITY OF UNIVERSITY SERVICES. © 2024 SEVENTH SENSE RESEARCH GROUP®